2005
DOI: 10.1677/joe.1.06014
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of 4-hydroxyestradiol to mouse uterine protein: evidence of a physiological role for 4-hydroxyestradiol

Abstract: There are several indications of a possible physiological role for 4-hydroxyestradiol (4-OHE 2 ) in hormone-responsive tissues. To examine a hormonal activity of 4-OHE 2 , we have studied the binding of 3 H-labeled 4-OHE 2 to mouse uterine cytosolic protein. In uteri of 3-week-old mice, total binding was 319·4 13·9 fmol/mg protein. Binding in the presence of excess unlabeled 4-OHE 2 dropped to 82·1 1·7 fmol/mg protein, whereas 214·6 9·4 fmol/mg protein bound while incubating in an excess of unlabeled 17 -estra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…gen metabolites, such as the well-known anticancer activity of 2-methoxy-E 2 [37,38], the unique actions of 4-hydroxy-E 2 [28,29], and the immunosuppressive effect of estriol [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gen metabolites, such as the well-known anticancer activity of 2-methoxy-E 2 [37,38], the unique actions of 4-hydroxy-E 2 [28,29], and the immunosuppressive effect of estriol [39].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 4-hydroxy-E 2 is a biologically active estrogen derivative [28,29], and PDI has a comparable binding affinity for E 2 and 4-hydroxy-E 2 (Fig. 1C).…”
Section: Pdi Slows Down Estrogen Metabolic Dispositionmentioning
confidence: 95%
“…In addition, 4OHE2 has been shown to bind to estrogen receptors with relative binding affinities of 26 to 42%, relative to E2 (Schutze et al, 1994). 4-OHE2-specific binding proteins, separate from the classical nuclear estrogen receptors, have also been characterized and may provide unique estrogenic activity (Das et al, 1998; Markides and Liehr, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Hepatic hydroxylation of E2 to catechols 2-OHE and 4-OHE in rats is catalyzed by CYP1A1/2, 1B1, 2B1/2, 2C11 and 3A (Yager and Liehr, 1996;Zhu and Conney, 1998;Dawling et al, 2003) and the subfamily CYP1B1 has been identified as a major enzyme catalyzing 4-hydroxylation of E2 (Markides and Liehr, 2005). Furthermore, 2-OHE can be metabolized to 2-methoxyestradiol that has an inhibitory effect on cell proliferation (Seegers et al, 1989;Fotsis et al, 1994;Klauber et al, 1997).…”
Section: Discussionmentioning
confidence: 99%